Model Kepemimpinan Lembaga Pendidikan Di Masa Pandem - Atika Permata Sari; Saipul Annur (Publikasi Indonesia, 2022)
In order to prevent the spread of the Corona virus, in Indonesia itself, a Large-Scale Social Restriction (PSBB) policy was implemented to suppress the spread of this virus, including in terms of education. Education applies social distancing which limits space and time to all routine activities in the learning system, the role of leaders is needed in directing, providing guidance, setting strategies or policies in an organization especially when in a pandemic emergency, a leadership model is needed in solving every problem especially in a pandemic emergency. The method used in this research is library research. The right leadership model in educational institutions during this pandemic is a situational leadership model, where this leadership model expresses how a manager's actions in certain situations his leadership can be effective.